2018
DOI: 10.15244/pjoes/85350
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Drought Stress on Yield, Yield Components, and Yield Stability at Different Growth Stages in Bread Wheat Cultivar (Triticum aestivum L.)

Abstract: Bread wheat (Triticum aestivum L.) is one of the most important cereal crops in the development of humans. Wheat, with about a 2.1 million km 2 total harvested area, is the most abundant crop in the world: it is the first rain-fed crop after maize and the second irrigated crop after rice [1]. With a total production that surpassed 700 million tons (MTons) in 2010, it is contributing to about the 20% of the total dietary calories and proteins worldwide [2, 3]. Compared to other important crops,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 17 publications
6
17
0
Order By: Relevance
“…These results indicated a considerable reduction in number of spikes/m 2 under combination of heat and drought stresses which, are in agreement with those reported by many wheat researchers e.g. Rebetzke et al (2008), Dreccer et al (2009), Dreccer et al (2012) and Mehraban et al (2019). Table 5.…”
Section: Number Of Spikes/msupporting
confidence: 91%
See 3 more Smart Citations
“…These results indicated a considerable reduction in number of spikes/m 2 under combination of heat and drought stresses which, are in agreement with those reported by many wheat researchers e.g. Rebetzke et al (2008), Dreccer et al (2009), Dreccer et al (2012) and Mehraban et al (2019). Table 5.…”
Section: Number Of Spikes/msupporting
confidence: 91%
“…Furthermore, this genotype can be utilized as a source for terminal heat and drought stresses or recommended for affected heat and drought stresses region. These results indicated that a detrimental effects on grain yield when heat and drought combined together than either alone these results in harmony with those obtained by Abro et al, (2019), Mehraban et al, (2019) and Feltaous et al, (2020). Consequently, selecting the most high yielding and stable genotype/s is an effective breeding strategy for heat and drought tolerance.…”
Section: Grain Yield/plot (Kg)supporting
confidence: 89%
See 2 more Smart Citations
“…Similarly, Karaman et al [24] compared irrigated and rainfed conditions, while Beres et al [25] considered both moisture and N fertilitisation in their studies in Canada. Other studies have also determined effects on grain morphology and/ or yield components [26,27], but less studies are available on the stability of grain compositon and quality. Both grain yield and some quality traits (thousand kernel weight, test weight, protein, starch, gluten, Zeleny, Alveograph) were determined to identify stable wheat genotypes in Turkey [28,29,30], and in India [31], while Silva et al [32] also considered the effect of the sowing dates on the stability of these traits in Brazil.…”
Section: Introductionmentioning
confidence: 99%